2017
DOI: 10.3390/nu9020105
|View full text |Cite
|
Sign up to set email alerts
|

Lychee Seed Saponins Improve Cognitive Function and Prevent Neuronal Injury via Inhibiting Neuronal Apoptosis in a Rat Model of Alzheimer’s Disease

Abstract: Lychee seed is a traditional Chinese medicine and possesses many activities, including hypoglycemia, liver protection, antioxidation, antivirus, and antitumor. However, its effect on neuroprotection is still unclear. The present study investigated the effects of lychee seed saponins (LSS) on neuroprotection and associated mechanisms. We established a rat model of Alzheimer’s disease (AD) by injecting Aβ25–35 into the lateral ventricle of rats and evaluated the effect of LSS on spatial learning and memory abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 42 publications
2
47
0
Order By: Relevance
“…Our previous studies have found that LSS can decrease the formation of Aβ and mitochondrial cytochrome C release, thereby inhibiting neuronal apoptosis in the brain of AD rats [51]. In the present study, we found that the anti-apoptotic effect of LSS in PC12 cells treated with Aβ 25-35 may be associated with mitochondrial membrane function and the NF-κB signaling pathway.…”
Section: Discussionsupporting
confidence: 61%
“…Our previous studies have found that LSS can decrease the formation of Aβ and mitochondrial cytochrome C release, thereby inhibiting neuronal apoptosis in the brain of AD rats [51]. In the present study, we found that the anti-apoptotic effect of LSS in PC12 cells treated with Aβ 25-35 may be associated with mitochondrial membrane function and the NF-κB signaling pathway.…”
Section: Discussionsupporting
confidence: 61%
“…BAD can increase mitochondrial permeability, release pro-apoptotic factors and CytC, and bind to Bcl-2 family proteins to form dimers, which trigger caspase signaling and cleave pro-caspase-3 into its active forms, resulting in neuronal apoptosis. 47 There is increasing evidence that oxidative stress and neuroinflammation play an important role in the mechanisms associated with Aβ-induced neurotoxicity in AD. 48 Aggregated Aβ may induce oxidative stress by causing mitochondrial dysfunction, which induces the release of reactive oxygen species (ROS), reduces antioxidant levels, such as those of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), etc., and increases oxidant levels, such as those of malondialdehyde (MDA).…”
Section: The Protective Effect Of Tf-ost-lip In Vivomentioning
confidence: 99%
“…In the current study, the AD animal model was established per our previously described method (Ma et al 2013;Wang et al 2017). In brief, normal male SD rats were first stereotaxically injected with 10 lg aggregated Ab 25-35 in the lateral ventricle at accurate positions based on the dorsoventral (DV), mediolateral (ML) and anteroposterior (AP) coordinates (respectively -2.8 mm, -2.2 mm and -3.0 mm), to locate the CA1 subregion of their hippocampus (Facchinetti et al 2018).…”
Section: Establishment Of the Ad Modelmentioning
confidence: 99%
“…The seeds of Litchi chinensis contain remarkable amounts of phenolic compounds such as protocatechuic acid, protocatechuic aldehyde, procyanidin D, (-)-epicatechin, cinnamtannin B1, procyanidin A1, rutin and phlorizin (Man et al 2016(Man et al , 2017. In addition, it also contains glycosides such as litchioside D, taxifolin 4 0 -O-b-D-glucopyranoside and kaempferol 7-O-neohesperidoside (Xu et al 2011;Wang et al 2017). Other categories such as organic acids, flavonoids, amino acids, fatty acids and sugar, are also fundamental chemical components of Litchi chinensis seeds (Guo and Pan 2006;Zhang and Zhang 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation